2017
DOI: 10.1103/physrevb.96.035437
|View full text |Cite
|
Sign up to set email alerts
|

Chirality blockade of Andreev reflection in a magnetic Weyl semimetal

Abstract: A Weyl semimetal with broken time-reversal symmetry has a minimum of two species of Weyl fermions, distinguished by their opposite chirality, in a pair of Weyl cones at opposite momenta ±K that are displaced in the direction of the magnetization. Andreev reflection at the interface between a Weyl semimetal in the normal state (N) and a superconductor (S) that pairs ±K must involve a switch of chirality, otherwise it is blocked. We show that this "chirality blockade" suppresses the superconducting proximity eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 36 publications
6
61
1
Order By: Relevance
“…4(b) and (c), where we have also taken the transverse momentum to be zero. As in the scattering matrix calculation, here again, the current oscillates as a function of both k 0 L/π and V 0 L/πv F , which clearly confirms the central result of our paper that inter-node Andreev reflection, if not prohibited by additional symmetries of the problem 32 , plays a crucial role in determining transport properties of the Weyl semimetalsuperconducting interface.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…4(b) and (c), where we have also taken the transverse momentum to be zero. As in the scattering matrix calculation, here again, the current oscillates as a function of both k 0 L/π and V 0 L/πv F , which clearly confirms the central result of our paper that inter-node Andreev reflection, if not prohibited by additional symmetries of the problem 32 , plays a crucial role in determining transport properties of the Weyl semimetalsuperconducting interface.…”
supporting
confidence: 88%
“…We summarize our results from the scattering matrix approach in Fig. 3 and we emphasize the following: first, the oscillation in the conductance is present even for normal-incidence, as expected from earlier results 13,21,32 which showed that the probability of normal-reflection at a WSM-SC junction is finite at normal incidence. Next, the oscillations in the conductance appear due to multiple reflections in the dot region, similar to those of a quantum mechanical double barrier problem.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Note.-During the review of our manuscript, we noticed the work of Bovenzi et al 58 . They study the normal and Andreev reflection processes at the junction of a WSM (with broken T symmetry) with a normal superconductor and observe that, while reflection within the same node is always blocked, Andreev reflection from one node to another can also be blocked at a WS junction if the interface or pair potential does not couple the two chiralities.…”
mentioning
confidence: 98%
“…(iii) Factors such as intervalley scattering, interfacial barrier, Fermi surface mismatch, and spatial profile of pair potential are inessential for the shift. And when symmetry argument applies, they have no effect on the value of the shift (as defined for a definite scattering process of the wavepacket), although they do affect the probability of the process [29,37].…”
mentioning
confidence: 99%